"Capacidad de liderazgo de Enfermería y satisfacción laboral en Enfermeras de hospitalización. Hospital Regional Docente de Trujillo - 2007." - Monzón Cosme, Dany Hilda (2007)
The present study of investigation of descriptive type-correlacional, had as objective, to describe and to analyze the relationship that exists between the Capacity of Leadership and the nurses' of hospitalization of Trujillo's Educational Regional Hospital Labor Satisfaction. The study population was constituted by 70 assistance nurses that work in the services of hospitalization. In the results it was found that significant statistical relationship of the Capacity of Leadership doesn't exist in the Labor satisfaction of the nurses of hospitalization. On the other hand, the Labor Satisfaction is of level “Half” in most of nurses that “If they have Capacity of leadership”, and they are capable to recognize the problems, to define them and to look for solutions and to achieve the goals proposed in each service of Trujillo's Educational regional Hospital.